2018
DOI: 10.1016/j.ophtha.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Can Macula and Optic Nerve Head Parameters Detect Glaucoma Progression in Eyes with Advanced Circumpapillary Retinal Nerve Fiber Layer Damage?

Abstract: Macula GCIPL and ONH parameters may be useful in tracking progression in patients with advanced glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 27 publications
4
34
0
1
Order By: Relevance
“…Cross-sectional studies have reported the "floor effect" of RNFL thickness at approximately 50 µm with Spectralis OCT, the level at which point no additional thinning can be distinguished [23][24][25] . Longitudinal studies have, however, shown that structural progression can still be seen in late stage disease and that the floor effects only occur at thinner RNFL values, which is in agreement with the present study 26,27 . Also, postmortem studies suggested that a few surviving ganglion cells remain detected in cases of advanced glaucoma 28 .…”
Section: Discussionsupporting
confidence: 93%
“…Cross-sectional studies have reported the "floor effect" of RNFL thickness at approximately 50 µm with Spectralis OCT, the level at which point no additional thinning can be distinguished [23][24][25] . Longitudinal studies have, however, shown that structural progression can still be seen in late stage disease and that the floor effects only occur at thinner RNFL values, which is in agreement with the present study 26,27 . Also, postmortem studies suggested that a few surviving ganglion cells remain detected in cases of advanced glaucoma 28 .…”
Section: Discussionsupporting
confidence: 93%
“…1 In our study, we demonstrated with OCT that eyes with advanced structural glaucomatous damage still had significant progression of macular ganglion-cell inner plexiform layer and optic nerve head parameters after reaching the minimal measurable circumpapillary retinal nerve fiber layer thickness (floor effect). 1 Using guided progression analysis (GPA), the commercially available progression detection tool, we also demonstrated that more eyes were labeled as progressing by the trend-based analysis with optic nerve head parameters and ganglion-cell inner plexiform layer compared with retinal nerve fiber layer thickness measurements. Our results are in agreement with a previous study that showed this progression pattern in the GPA trend analysis also occurs at earlier stages of the disease.…”
mentioning
confidence: 59%
“…The interpretation of this finding is discussed in our article. 1 Unfortunately, we cannot address the discrepancy with Dr Hwang's unpublished data on the optic nerve head analysis without having the ability to evaluate these results. Nevertheless, we are in full agreement with Dr Hwang's conclusion that further studies are required to optimize clinical evaluation in advanced glaucoma.…”
mentioning
confidence: 86%
“…Therefore, a more frequent trend-based progression in GCIPL than RNFL implies GCIPL may have a tendency for diffuse-type progression compared with RNFL, which may tend to show localized-type progression. 2 In the study from Lavinsky et al, 1 when eventbased OCT GPA analysis was used, more frequent progression was found in RNFL (31 eyes) compared with GCIPL (10 eyes), which is in contrast with the trend-based analysis. Thus, these results may be interpreted as, "In advanced stages of glaucoma, trend-based progression was more frequently found in GCIPL and ONH than in RNFL and event-based progression was more commonly found in RNFL than in GCIPL."…”
mentioning
confidence: 97%